Telomere Maintenance Associated Mutations in the Genetic Landscape of Gynecological Mucosal Melanoma - Yuan, Guangwen; Song, Jinge; Li, Ning; Song, Qianqian; Li, Yifei; Du, Yingxi; Wang, Xiaobing; Jiao, Yuchen; Wu, Lingying (Frontiers in Oncology, 2020)
Purpose: Gynecological melanomas (GMs) are rare tumors with a poor prognosis. Here, we performed exome sequencing to generate the mutational landscape of GMs. Methods: Next-generation sequencing (NGS) was carried out on mucosal melanoma samples (n = 35) obtained from gynecological sites. The Alternative telomere lengthening (ALT) phenotype was verified by fluorescence in situ hybridization (FISH) and the C-circle assay. Immunohistochemistry (IHC) was performed to detect ATRX protein. Copy number variations in TERT were detected by droplet digital PCR (ddPCR). Results: In the 58 formalin-fixed-paraffin-embedded (FFPE) samples, we identified 33 (56.9%) ALT-positive cases with 23 showing loss of ATRX protein. TERT promoter mutation was not detected in GMs (n = 40), but copy number variations in the TERT region were observed in 20% (7/35) of the samples. TERT amplification was mutually exclusive with ALT (P < 0.05). Kaplan-Meier revealed that ALT relative to TERT amplification was associated with longer overall survival (OS) in GM patients without metastasis. Conclusion: These findings indicate that telomere maintenance mechanisms (TMMs) play a critical role in the tumorigenesis of GMs and may aid in the prediction of clinical prognosis and the development of targeted therapy for the treatment of GM.